Phase transformation mechanism of oxidation roasting of low-grade polymetallic chalcopyrite ore in the presence of CaO - Ma, Haifei; Liao, Yalong; WU, Min; Jia, Xiaobao; Yang, shuangyu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Low-grade polymetallic chalcopyrite ore has a high lead and iron content and a low softening point, which is difficult to treat using conventional pyrometallurgical and hydrometallurgical processes. In order to investigate the suitable methodology for efficient utilization, it was pelletized with CaO for oxidation roasting in the present work. By controlling the Po2 and Pso2 in the gas phase, the metal sulfide in the ore was converted into easily soluble metal oxide, the thermal analysis of the roasting process was carried out and the acid leaching of the extracted calcine at atmospheric pressure was investigated. The results show that by pelletizing with CaO and then roasting at 800 ℃ for 1 h, chalcopyrite is converted into CuO, which can be easily dissolved, galena and pyrite are converted into PbO2 and Fe2O3, respectively, and sulfur reacts with CaO and turns into CaSO4, which can fix the sulfur in the calcine. The copper leaching rate of calcine can reach 98.60 wt.% under atmospheric pressure in the H2SO4-H2O system. CaO can increase the softening point of raw materials, improve the roasting effect, promote the phase transformation of chalcopyrite in the oxidation process, and convert sulfur into CaSO4 to fix sulfur, effectively avoiding SO2 pollution to the environment.